2007
DOI: 10.1128/jvi.02406-06
|View full text |Cite
|
Sign up to set email alerts
|

Murine Gammaherpesvirus 68 Contains Two Functional Lytic Origins of Replication

Abstract: A 1.25-kbp DNA fragment from the right side of the genome containing the lytic origin of replication (oriLyt) of murine gammaherpesvirus 68 (MHV-68) has been identified by a plasmid replication assay. Here we show that a mutant MHV-68 with a deletion of an essential part of this oriLyt, generated by using an MHV-68 bacterial artificial chromosome, was only slightly attenuated and still able to replicate but that a mutant containing an additional deletion on the left side of the genome was replication deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In addition, it was shown previously that KSHV RTA binds to the left oriLyt and regulates oriLyt-associated transcription (60,61). As for MHV-68, we and another group have previously identified two oriLyt regions (2,20,28). We have further mapped the minimal region of the left oriLyt to nucleotides (nt) 25695 to 26883 (28).…”
mentioning
confidence: 99%
“…In addition, it was shown previously that KSHV RTA binds to the left oriLyt and regulates oriLyt-associated transcription (60,61). As for MHV-68, we and another group have previously identified two oriLyt regions (2,20,28). We have further mapped the minimal region of the left oriLyt to nucleotides (nt) 25695 to 26883 (28).…”
mentioning
confidence: 99%
“…Defects in latent gene expression and impaired immune evasion might explain the phenotype of the Delta 40 bp repeat mutant, yet there are also other possibilities: First, we have recently demonstrated that the 40 bp repeat forms part of one lytic origin of MHV-68 [59]. Thus, although having no effect in vitro , deletion of the 40 bp repeat might lead to impairment of viral reactivation in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…While this manuscript was in preparation, Adler et al reported identification of a relatively large region which contains a second ori Lyt in MHV-68 (Adler et al, 2007). In our independent study, we first employed a high density transposon-mediated mutagenesis method to fine-map cis -elements essential for the MHV-68 right ori Lyt.…”
Section: Introductionmentioning
confidence: 99%